Healing and medical practice in Ancient Egypt, or: What can be done in four days? - Di Biase-Dyson, Camilla; Schultz, Michael; Wagenknecht, Nina (Romanitas - Revista de Estudos Grecolatinos, 2025)
This paper considers what time periods appear in Ancient Egyptian medical texts and why these specifi c time periods are mentioned, an issue that has been sparingly addressed in the literature to date. The study supplies a quantitative analysis of time periods in their textual context and considers what the ‘four-day’ time period could potentially be referring to, given current medical knowledge on the topic of healing. It considers a range of theories about the time periods with reference to two case studies, on time periods in the medical Papyrus Hearst and on time periods other than four days across the pharaonic medical corpus. It considers the mythical context of the number four and concludes with an overview of whether changes in medical and religious traditions after the pharaonic period led to the use of new numbers in healing texts.